1987
DOI: 10.1159/000163418
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Sodium Butyrate and Dimethylsulfoxide on Gamma-Glutamyl Transpeptidase and Alkaline Phosphatase Activities in MCF-7 Breast Cancer Cells

Abstract: Sodium butyrate and dimethylsulfoxide (DMSO), two known chemical inducers of cell differentiation, were examined on MCF-7 breast cancer cells. Both agents reduce the proliferative capacity of MCF-7 cells, as reflected by inhibition of colony formation in semi-solid agar. Sodium butyrate is shown to enhance markedly the activity of two plasma membrane-bound enzymes, alkaline phosphatase and γ-glutamyl transpeptidase. DMSO does not enhance the activity of these enzymes, but rather induces a small decrease in γ-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…Most studies were performed on the MCF-7 breast cancer cell line and selected experiments were done with the T-47D cell line. Cells were cultured as previously described (Wasserman et al, 1987). For growth experiment cells (105 ml -1) were plated in culture medium (1.5ml-RPMI 1640 supplemented with 10% foetal calf serum and antibiotics) in the absence and presence of MA.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were performed on the MCF-7 breast cancer cell line and selected experiments were done with the T-47D cell line. Cells were cultured as previously described (Wasserman et al, 1987). For growth experiment cells (105 ml -1) were plated in culture medium (1.5ml-RPMI 1640 supplemented with 10% foetal calf serum and antibiotics) in the absence and presence of MA.…”
mentioning
confidence: 99%
“…Lipid staining by the oil red 0 method (Pearse, 1968) revealed that MA induced lipid accumulation within the cells (Figure 2). The activity of the glycoprotein membrane-bound enzyme alkaline phosphatase was measured as previously described (Wasserman et inducers of differentiation (Wasserman et al, 1987). The effect of MA on lipid accumulation is shared by the differentiating agents dimethylsulphoxide and sodium butyrate (Costlow, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The applicability of this method to other species or other types of intestinal damage, such as those associated with inflammatory processes, requires further investigation. In this context, it should be noted that GGT in different cell types is subject to phenotypic alterations induced by different agents (Novogrodsky et al, 1976;Wasserman et al, 1987;Sidi et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, colon carcinoma HT-29 cells may be reversibly differentiated into enterocytes or mucin-producing lineages (Chakrabarty et al, 1992;Choi et al, 2000;Demers et al, 2009), and another colon carcinoma SW1222 cells differentiate into enterocytes, enteroendocrine and goblet cells (Yeung et al, 2010). Yet another classical example is breast carcinomas such as MCF-7 cells which may also be induced to differentiate by sodium butyrate and forskolin (Wasserman et al, 1987;Guilbaud et al, 1990). Conversely, nuclear transfer studies showed that the phenotype of at least some cancer cells (as shown for melanomas) can be reversed to a pluripotent state that allows apparently normal differentiation (Hochedlinger et al, 2004).…”
Section: Properties Of Stem Cells and Cscs: Similarities And Differencesmentioning
confidence: 99%